Character instrumentation of environmental care for children aged 4-5 based on digital media - Hartati, H; Katoningsih, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to explain how digital media can be used to foster environmental‑care attitudes in preschool children at Firdausy Kindergarten and to identify the key factors that influence the success of such initiatives. Methodology: A qualitative case‑study approach was adopted, involving systematic collection of classroom photographs and direct observations of learning activities that leveraged interactive games and videos. Semi‑structured interviews were conducted with kindergarten leaders and teachers engaged in the project, and relevant documents (lesson plans, activity logs) were reviewed. Data analysis followed three phases—data reduction, data visualization, and inferential synthesis—to surface themes related to media use and program efficacy. Results: Findings indicate that incorporating digital media—specifically interactive environmental games and educational videos— significantly heightened children’s understanding of why and how to protect their surroundings. Moreover, the project’s success was bolstered by strong parental involvement, which extended learning beyond the classroom, and by carefully curated, high‑quality teaching materials that complemented the digital content. Applications/Originality/Value: By demonstrating a replicable model for integrating digital tools into early‑childhood environmental education, this research provides actionable insights for curriculum developers and preschool educators. Its emphasis on stakeholder engagement (parents and teachers) and media quality offers a holistic framework for designing future programs that not only engage young learners but also build sustainable eco‑responsibility from the earliest stages of schooling.